(untitled) (Baghdad Science Journal, 2012)
The plant Zizyphus spina-christa grows wildly in the middle and southern of Iraq locally named Nabag. In this study the antibacterial activity of several different plant extract (alcoholic hot and cold extract 80%, aqueous hot and cold extract) was tested against some gram negative bacteria that related to Enterobacteriacea as follow; Pseudomonas aeruginosa, Escherchia coli Proteus mirabilis, Serratia mercesence,. Aeromonas sp, Klebsiella pneumoniae ,Shigella sp, Salmonella enteritidis (134), S. typhi(97), S. typhimurium (300) , S. typhi, . The results showed that efficient method of extract was alcoholic hot extract from other extract methods that are used in this study. The detection of active compound in crude extracts of the leaves showed positive reaction for alkaloids, flavonoides, saponin,peptides, tannins and carbohydrates , while the aqueous hot and cold extract did not give any reaction against terpenes ,resins and coumarins . Minimum inhibitory concentration (MIC) of the ethanolic hot extracts of plants was determined and the results showed that MIC of S.typhi was 25 mg / ml and 250 mg/ml aganist Klebsiella pneumoniae Serratia mercesence , Pseudomonas aeruginosa , while other isolates showed variety in their inhibitory action. the ethanolic hot extracts of plants did not show any bacteriocidal effect against all bacteria that included in this study within concentration that used except S. typhi in concentration 50 mg/ml . The effect of Sub – MIC of the ethanolic hot extract of plant on the production of some virulence factors from selective isolates S. typhi ,showed an inhibitory effect on production of H2S but no effect on others characteristic such, mannitol and glucose fermenter at 20 mg / ml . The electrophoresis of plasmid DNA isolated from bacterial cell treated with, alcoholic hot extract at sub-MIC concentrations had a curing effect on the plasmid of S. typhi .Using infrared spectroscopy spectrum indicates the possible effect of alcoholic hot extract on the conformation of the DNA molecules affecting some of its biological functions.